Antioxidative Potential of a Streptomyces sp. MUM292 Isolated from Mangrove Soil. (1st April 2018) - Tan, Loh Teng-Hern; Chan, Kok-Gan; Chan, Chim Kei; Khan, Tahir Mehmood; Lee, Learn-Han; Goh, Bey-Hing
Abstract : Mangrove derived microorganisms constitute a rich bioresource for bioprospecting of bioactive natural products. This study explored the antioxidant potentials of Streptomyces bacteria derived from mangrove soil. Based on 16S rRNA phylogenetic analysis, strain MUM292 was identified as the genus Streptomyces . Strain MUM292 showed the highest 16S rRNA gene sequence similarity of 99.54% with S. griseoruber N B R C 12873 T . Furthermore, strain MUM292 was also characterized and showed phenotypic characteristics consistent with Streptomyces bacteria. Fermentation and extraction were performed to obtain the MUM292 extract containing the secondary metabolites of strain MUM292. The extract displayed promising antioxidant activities, including DPPH, ABTS, and superoxide radical scavenging and also metal-chelating activities. The process of lipid peroxidation in lipid-rich product was also retarded by MUM292 extract and resulted in reduced MDA production. The potential bioactive constituents of MUM292 extract were investigated using GC-MS and preliminary detection showed the presence of pyrazine, pyrrole, cyclic dipeptides, and phenolic compound in MUM292 extract. This work demonstrates that Streptomyces MUM292 can be a potential antioxidant resource for food and pharmaceutical industries.